Implementation of an Enzyme Membrane Reactor to Intensify the α-O-Glycosylation of Resveratrol Using Cyclodextrins - Irina Ioannou; Eduardo Barboza; Gaëlle Willig; Thomas Marié; Andreïa Texeira; Pierre Darme; Jean-Hugues Renault; Florent Allais (MDPI AG, 2021)
The O-glycosylation of resveratrol increases both its solubility in water and its bioavailability while preventing its oxidation, allowing a more efficient use of this molecule as a bioactive ingredient in pharmaceutical and cosmetic applications. Resveratrol O-glycosides can be obtained by enzymatic reactions. Recent developments have made it possible to selectively obtain resveratrol α-glycosides from the β-cyclodextrin-resveratrol complex in water with a yield of 35%. However, this yield is limited by the partial hydrolysis of the resveratrol glycosides produced during the reaction. In this study, we propose to intensify this enzymatic reaction by coupling the enzymatic reactor to a membrane process. Firstly, membrane screening was carried out at the laboratory scale and led to the choice of a GE polymeric membrane with a cut-off of 1 kDa. This membrane allowed the retention of 65% of the β-cyclodextrin-resveratrol complex in the reaction medium and the transfer of 70% of the resveratrol α-O-glycosides in the permeate. In a second step, this membrane was used in an enzymatic membrane reactor and improved the yield of the enzymatic glycosylation up to 50%.